РЕАЛИСТИК ТАСВИР ВА БАДИИЙ МАҲОРАТ - Матякупов, С. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of realistic analysis of literary skill in Uzbek prose. There were also analysed the writer’s style, his mastery, creative individuality on the basis of concrete examples on the basis of the analysis of artistic peculiarities of the creative activity of Nazar Eshankul.
Keywords: individuality; literary interpretation; literary; idea; philosophic interpretation